Activity and safety of brigatinib in ALK-rearranged non-small-cell lung cancer and other malignancies: a single-arm, open-label, phase 1/2 trial. Issue 12 (December 2016) - Gettinger, Scott N; Bazhenova, Lyudmila A; Langer, Corey J; Salgia, Ravi; Gold, Kathryn A; Rosell, Rafael; Shaw, Alice T; Weiss, Glen J; Tugnait, Meera; Narasimhan, Narayana I; Dorer, David J; Kerstein, David; et al.
Summary: Background: Anaplastic lymphoma kinase ( ALK ) gene rearrangements are oncogenic drivers of non-small-cell lung cancer (NSCLC). Brigatinib (AP26113) is an investigational ALK inhibitor with potent preclinical activity against ALK mutants resistant to crizotinib and other ALK inhibitors. We aimed to assess brigatinib in patients with advanced malignancies, particularly ALK -rearranged NSCLC. Methods: In this ongoing, single-arm, open-label, phase 1/2 trial, we recruited patients from nine academic hospitals or cancer centres in the USA and Spain. Eligible patients were at least 18 years of age and had advanced malignancies, including ALK -rearranged NSCLC, and disease that was refractory to available therapies or for which no curative treatments existed. In the initial dose-escalation phase 1 stage of the trial, patients received oral brigatinib at total daily doses of 30–300 mg (according to a standard 3 + 3 design). The phase 1 primary endpoint was establishment of the recommended phase 2 dose. In the phase 2 expansion stage, we assessed three oral once-daily regimens: 90 mg, 180 mg, and 180 mg with a 7 day lead-in at 90 mg; one patient received 90 mg twice daily. We enrolled patients in phase 2 into five cohorts: ALK inhibitor-naive ALK -rearranged NSCLC (cohort 1), crizotinib-treated ALK -rearranged NSCLC (cohort 2), EGFR T790M -positive NSCLC and resistance to one previous EGFR tyrosine kinase inhibitor (cohort 3), other cancers with abnormalities in brigatinib targets (cohort 4), and crizotinib-naive or crizotinib-treated ALK -rearranged NSCLC with active, measurable, intracranial CNS metastases (cohort 5). The phase 2 primary endpoint was the proportion of patients with an objective response. Safety and activity of brigatinib were analysed in all patients in both phases of the trial who had received at least one dose of treatment. This trial is registered withClinicalTrials.gov, numberNCT01449461 . Findings: Between Sept 20, 2011, and July 8, 2014, we enrolled 137 patients (79 [58%] with ALK -rearranged NSCLC), all of whom were treated. Dose-limiting toxicities observed during dose escalation included grade 3 increased alanine aminotransferase (240 mg daily) and grade 4 dyspnoea (300 mg daily). We initially chose a dose of 180 mg once daily as the recommended phase 2 dose; however, we also assessed two additional regimens (90 mg once daily and 180 mg once daily with a 7 day lead-in at 90 mg) in the phase 2 stage. four (100% [95% CI 40–100]) of four patients in cohort 1 had an objective response, 31 (74% [58–86]) of 42 did in cohort 2, none (of one) did in cohort 3, three (17% [4–41]) of 18 did in cohort 4, and five (83% [36–100]) of six did in cohort 5. 51 (72% [60–82]) of 71 patients with ALK -rearranged NSCLC with previous crizotinib treatment had an objective response (44 [62% (50–73)] had a confirmed objective response). All eight crizotinib-naive patients with ALK -rearranged NSCLC had a confirmed objective response (100% [63–100]). Three (50% [95% CI 12–88]) of six patients in cohort 5 had an intracranial response. The most common grade 3–4 treatment-emergent adverse events across all doses were increased lipase concentration (12 [9%] of 137), dyspnoea (eight [6%]), and hypertension (seven [5%]). Serious treatment-emergent adverse events (excluding neoplasm progression) reported in at least 5% of all patients were dyspnoea (ten [7%]), pneumonia (nine [7%]), and hypoxia (seven [5%]). 16 (12%) patients died during treatment or within 31 days of the last dose of brigatinib, including eight patients who died from neoplasm progression. Interpretation: Brigatinib shows promising clinical activity and has an acceptable safety profile in patients with crizotinib-treated and crizotinib-naive ALK -rearranged NSCLC. These results support its further development as a potential new treatment option for patients with advanced ALK -rearranged NSCLC. A randomised phase 2 trial in patients with crizotinib-resistant ALK -rearranged NSCLC is prospectively assessing the safety and efficacy of two regimens assessed in the phase 2 portion of this trial (90 mg once daily and 180 mg once daily with a 7 day lead-in at 90 mg). Funding: ARIAD Pharmaceuticals.